Potential of Membrane Distillation for Water Recovery and Reuse in Water Stress Scenarios: Perspective from a Bibliometric Analysis - Romero-Figueroa, J; Quijada-Maldonado, E; Abejon-Elias, R (Elsevier B.V., 2024)
Climate change and related issues such as water scarcity and the urgent need for a transition to sustainable energy sources have motivated the development of novel processes and techniques that can be applied for water treatment, recovery and reuse. Among these emerging processes, membrane distillation in its different configurations has been extensively studied and reported in the literature. A bibliometric analysis was performed to investigate the research documents published in the scientific database Scopus until 2024, related to use of membrane distillation for water recovery and reuse. The main quantitative attributes of the research during this period were identified. The results of this analysis showed a very low scientific production until 2005, followed by a rapid exponential increase since then. The combined contribution of the two most productive countries (China and USA respectively) accounted for more than 41 % of the total number of publications, followed by Australia and Saudi Arabia, which occupied the third and fourth positions in the ranking. Chemical engineering was the most important subject category (57.4 % contribution), closely followed by environmental sciences. The review of the most cited documents and keywords showed that membrane wetting is one of the main drawbacks that can reduce the performance of membrane distillation and the use of innovative superhydrophobic, omniphobic or Janus membranes resulted an adequate solution to avoid this problem. Moreover, the desalination of seawater, brines and other highly saline solutions can be considered as the most studied application of membrane distillation. The consideration of the energetic aspects of membrane distillation and its coupling with other technologies were identified as relevant topics during the bibliometric network analysis. Special attention was given to the potential of membrane distillation for water recovery and reuse in the Chilean context of water stress for the production of drinking water and the treatment of domestic greywater and wastewater from mining and other industrial activities. © 2024 Elsevier B.V.